Coral recruitment success and sessile benthic colonisation estimation in Tioman Island Marine Park, Malaysia - Muhammad Faiz, Mohd Hanapiah; Shahbudin, Saad; Mukai, Yukinori (Springer Netherlands, 2017)
This study examined the implementation of designated artificial reef plates made of coral rubble, sand and plasters cement as a potential substrate in order to optimise the recruitment success at four reef sites in Tioman Island in Malaysia, namely Genting Village, Renggis Island, Teduh Bay and Juara Bay between April 2012 and June 2013. Recruitment was dominated by Acroporidae (65.48%), followed by Pocilloporidae (31.4%), Faviidae (2.34%), Poritidae (0.89%) and Fungiidae (0.19%). Terracotta tiles had significantly higher recruitment densities compared to artificial reef plates, and were further compared to artificial reef plates at each reef site (Mann Whitney U = 983.5, Z = −3.43, ρ < 0.05) during the initial settlement period. However, no significant difference was observed between both types of plates during the post-settlement period. Artificial reef plates exhibited a higher mean total benthic percentage cover compared to terracotta tiles during both settlement periods. These results might provide significant information on a proper substrate in order to optimise coral settlement.